2012
DOI: 10.4103/0976-9668.95944
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between lipid and lipoprotein metabolism in trimesters of pregnancy in Nigerian women: Is pregnancy a risk factor?

Abstract: Background:Changes in lipid metabolism have been shown to occur during pregnancy, to ensure a continuous supply of nutrients to the growing fetus, despite intermittent maternal food intake. Abnormal lipid metabolism has also been linked to atherosclerosis.Objective:To investigate the effect of pregnancy on the lipid profile and possible predisposition of pregnant Nigerian women to atherosclerosis.Settings and Design:Serum lipid and lipoprotein levels of 60 apparently healthy pregnant women aged between 25 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 23 publications
1
11
3
Order By: Relevance
“…The mean value being raised above 2 folds in HPW compared to NNPW. HDL-C, LDL-C and VLDL-C also increased significantly (p<0.001).This agrees partly with Neboh et al, (2012) and Udoh, et al, (2002) [19,20] , who observed a progressive increase in TG, HDL-C, LDL-C, VLDL-C and TC at various stages of pregnancy; even if we did not specify the stages of pregnancy in this work, but in contrast to their finding, TC was not significant. The mean increase in TG levels in HPW and NPW are higher than that of NNPW because of estrogen levels in pregnancy.…”
Section: Discussionsupporting
confidence: 88%
“…The mean value being raised above 2 folds in HPW compared to NNPW. HDL-C, LDL-C and VLDL-C also increased significantly (p<0.001).This agrees partly with Neboh et al, (2012) and Udoh, et al, (2002) [19,20] , who observed a progressive increase in TG, HDL-C, LDL-C, VLDL-C and TC at various stages of pregnancy; even if we did not specify the stages of pregnancy in this work, but in contrast to their finding, TC was not significant. The mean increase in TG levels in HPW and NPW are higher than that of NNPW because of estrogen levels in pregnancy.…”
Section: Discussionsupporting
confidence: 88%
“…While blood lipid concentrations after pregnancy were not available in this cohort, other research has indicated that lipid concentrations return to pre-pregnancy concentrations after delivery, suggesting that the increase in blood lipids could have an important role in the development of the fetus [ 3 , 23 , 24 ]. This is further supported by research highlighting that the increase in blood lipids during pregnancy is not associated with an increased risk of atherosclerosis in women [ 3 , 25 ]. In fact, raised HDL-C may have a role in protecting the maternal vascular endothelium during pregnancy [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 74%
“…An atherogenic profile is an important risk factor for coronary diseases ( 57 , 58 ) . However, changes in serum lipoproteins cannot always be associated with dyslipidaemias; for example, pregnant women show increased serum lipid content but a low cardiac risk factor ( 59 ) ; the AI is higher in postmenopausal women ( 60 ) ; the lipid profile is atherogenic during pregnancy and lactation in Sprague–Dawley rats ( 61 ) ; high-sucrose and high-fat diets increase TAG in the serum and liver, as well as circulating cholesterol and LDL ( 62 ) . According to our results, the DRF group showed a decrease in AI in spite of high LDL levels; this can be explained by the low TAG concentrations in the DRF group (Table 2).…”
Section: Discussionmentioning
confidence: 99%